Correlation Analysis of Teachers' Health Literacy and Cardiovascular Risk Factors: A Spearman Rank Study - Siti Rohimah; Ira Sartika; Dedeng Nurkholik Sidik Permana (Universitas Galuh, 2025)
Hypertension and hypercholesterolemia are major cardiovascular risk factors that can be prevented through healthy behaviors. This study aims to analyze the correlation between teachers' knowledge of CERDIK behavior (Check health, Eliminate smoking, Be physically active, Healthy diet, Get enough rest, Manage stress) and the incidence of hypertension and hypercholesterolemia in high schools in Ciamis Regency. The study employed a descriptive quantitative correlational design with a cross-sectional approach. The sample consisted of 72 teachers selected through purposive random sampling. Data collection included a CERDIK behavior knowledge questionnaire, blood pressure measurement, and cholesterol level examination. Spearman Rank correlation test showed a significant correlation between CERDIK behavior knowledge and the incidence of hypertension (p = 0.000; r = 0.695) and hypercholesterolemia (p = 0.000; r = 0.622) with a strong correlation strength (0.60-0.799). In conclusion, improving teachers' health literacy is crucial to support cardiovascular disease prevention. Further research should explore school-based health education interventions.